2011
DOI: 10.1007/s10661-011-2416-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution behavior and carcinogenic level of some polycyclic aromatic hydrocarbons in roadside soil at major traffic intercepts within a developing city of India

Abstract: A study of polycyclic aromatic hydrocarbons (PAHs) pollution in roadside soil was conducted at a developing city locations of Jalandhar (Punjab), India in winter season to ascertain the contamination levels and their distribution behavior in roadside soil. PAHs concentration level of ten locations was measured at 1, 2, and 3 m distances from roadside soil covering all the major traffic intercepts within a city. Samples were extracted in acetone and dichloromethane (1:1) using soxhlet extraction. The extracts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…the data synthesized by Marusenko et al (2011). The influence of traffic density was also supported by the results of Kumar and Kothiyal (2012), and to a lesser extent Marusenko et al (2011); in the latter case, the most influent factor was found to be soil organic matter. Conversely, Agarwal (2009) noticed a lack of correlation between total PAH concentrations and the soil's organic carbon, and stated that the variations of concentrations could be explained in terms of vehicular composition (two-wheelers, cars, heavy-duty vehicles), as well as immediate surroundings of the road that modify atmospheric transport mechanisms.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…the data synthesized by Marusenko et al (2011). The influence of traffic density was also supported by the results of Kumar and Kothiyal (2012), and to a lesser extent Marusenko et al (2011); in the latter case, the most influent factor was found to be soil organic matter. Conversely, Agarwal (2009) noticed a lack of correlation between total PAH concentrations and the soil's organic carbon, and stated that the variations of concentrations could be explained in terms of vehicular composition (two-wheelers, cars, heavy-duty vehicles), as well as immediate surroundings of the road that modify atmospheric transport mechanisms.…”
Section: Introductionmentioning
confidence: 54%
“…Spatial patterns of PAHs, however, do not appear to be as systematic as for metals: while Yang et al (1991) observed a consistently decreasing trend with increasing distance from the road, in other studies, the highest PAH concentrations were not always measured close to the road edge (Dierkes and Geiger, 1999;Marusenko et al, 2011;Piguet et al, 2008). Kumar and Kothiyal (2012), who analyzed soil samples collected at 1, 2, and 3 m from various roads, even found different patterns depending on the considered compound. For both metals and PAHs, it appears necessary to better characterize the spatial distribution of soil contamination in the first 2-3 meters from the road, so as to identify, where applicable, the area subject to the highest accumulation.…”
Section: Introductionmentioning
confidence: 74%
“…The total population of Jalandhar was 2,193,590 according to 2011 census and it was projected to be 2,383,415 by 1st of October 2018. The District is interconnected by roads and is known for agriculture, textile industry, wood products, and spare parts of automobiles [22]. The samples were collected close to the National Highways roads connecting Jalandhar with Jammu and Amritsar, and Amritsar.…”
Section: Study Areamentioning
confidence: 99%
“…distribution behavior of PAH were investigated during winter in roadside soil at major traffic intercepts within a developing city of Punjab, India (Kumar and Kothiyal, 2012). Average concentrations of 16 PAHs decreased with distance from 1 to 3 m at high traffic density intersections.…”
Section: Soil Contamination Contamination Levels Andmentioning
confidence: 99%